THE INFLUENCE OF SOCIAL STATUS OF WOMEN ON BIRTH INTERVAL IN INDONESIA - Desy Nuri Fajarningtiyas (Widyariset, 2012)
The median of birth interval in Indonesia is quite high which is 43,7 months. This figure can be classified asan ideal birth interval. However, the percentage point of the number of ideal birth interval only increases slowly(0,06 % annually). The findings of previous studies revealed that women’s status affected birth interval. Thus, thecurrent research aims to identify the influence of women’s status on birth interval in Indonesia context. The dataemployed in this study is taken from the 2007 Indonesia Demographic and Health Survey. The number of sampleused is 32.985 ever married women. The multinomial logistic regression is chosen for analysing the data since thedependent variables (birth interval) are categorical. The results of this study shows that educational level, wealthindex and the involvement of women in decision making related to the health services acquirement influences birthinterval.